2018
DOI: 10.1016/j.psychres.2018.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Social-cognitive risk factors for violence in psychosis: A discriminant function analysis

Abstract: It has been proposed that mixed findings in studies investigating social cognition as a risk factor for violence in psychosis may be explained by utilizing a framework distinguishing between social-cognitive tests which measure relatively more basic operations (e.g. facial affect recognition) and measures of more complex operations (mentalizing, metacognition). The current study investigated which social cognitive and metacognitive processes are related to a violent history over and above illness-related defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Furthermore, Liberman (2012) argues that personal recovery is not a scientific construct and should therefore not be measured as an outcome in research. In an opinion paper, Bellack (2006) observed that the validity of self‐assessment of personal experiences can be argued in patients with psychosis because of impaired reasoning and reality distortion (Bellack 2006; de Jong et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Liberman (2012) argues that personal recovery is not a scientific construct and should therefore not be measured as an outcome in research. In an opinion paper, Bellack (2006) observed that the validity of self‐assessment of personal experiences can be argued in patients with psychosis because of impaired reasoning and reality distortion (Bellack 2006; de Jong et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Empathic Accuracy Task (EAT [ 32 ]; Dutch version [ 33 ]) is a computerized video task measuring empathy, with clips of people speaking about emotionally charged autobiographical events with either a positive or a negative valence. Conforming to previous studies [ 34 , 35 ], a shortened version (4 videos; 2 positive and 2 negative) was used. Parallel versions were administered, using counterbalanced randomization.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have found metacognition predicted social functioning prospectively over a 5-month interval (Lysaker et al, 2011b) and that changes in metacognitive capacity were associated with improvements in social skills (Inchausti et al, 2017a). Support for a link between metacognition and social functioning can also be found in research suggesting that metacognitive deficits predict multiple psychological constructs and biological processes believed to be cornerstones of social functioning, including intrinsic motivation (Luther et al, 2016(Luther et al, , 2017, complexity of social schema (Lysaker et al, 2010b), anhedonia (Buck et al, 2014), aggression (de Jong et al, 2018), sense of social connection (Kukla, Lysaker, & Salyers, 2013), empathy (Bonfils, Lysaker, Minor, & Salyers, 2018;WeiMing, Yi, Lysaker, & Kai, 2015), and levels of oxytocin (Aydin, Lysaker, Balıkçı, Ü nal-Aydın, & Esen-Danacı, 2018).…”
Section: Introductionmentioning
confidence: 95%